Предмет: Математика,
автор: fedorovaliuda2
6*(b-3)=10-2*(b=2) htibnm ehfdytybt
Ответы
Автор ответа:
0
6b-18=10-2b+4
6b+2b=18+10+4
8b=32
b=4
6b+2b=18+10+4
8b=32
b=4
Автор ответа:
0
6(b-3)=10-2(b-2)
6b-18=10-2b+4
6b+2b=10+18+4
8b=32
b=4
Ответ: 4
6b-18=10-2b+4
6b+2b=10+18+4
8b=32
b=4
Ответ: 4
Автор ответа:
0
Большое спасибо!
Похожие вопросы
Предмет: Математика,
автор: shumkov910
Предмет: Английский язык,
автор: gustxgod
Предмет: Русский язык,
автор: Аноним
Предмет: Математика,
автор: 2683226
Предмет: Математика,
автор: fguliyev